Integración morfométrica y molecular para la resolución del estatus taxonómico de las poblaciones de San Andrés y Providencia (Mar Caribe) pertenecientes a los géneros Poecilia y Gambusia (Teleostei: Poeciliidae) (2016)
In San Andrés and Providencia islands (western Colombian Caribbean) are registered two poeciliid fishes: Gambusia aestiputeus and Poecilia vetiprovidentiae. However, these have been considered conespecific with Poecilia sphenops (Valenciennes, 1846) and Gambusia nicaraguensis (Günther, 1866) even though it has been proposed to review their situation, due to the great geographic variations and the taxonomic difficulties presented by these two genera. In this way, the present work evaluated the morphometric and mitochondrial variation for Cit-B and NADH genes, of Gambusia and Poecilia populations respectively, present in the Colombian islands. We found significant differences in size and conformation, where populations with the largest individuals are in Providence. Likewise, for mitochondrial variation we found both G. aestiputeus and P. vetiprovidentiae are not conespecific whit G. nicaraguensis and P. sphenops respectively for the markers used.